1999
DOI: 10.1074/jbc.274.17.11782
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of Disulfide Bonds Is Responsible for Impaired Secretion in Human Complement Factor H Deficiency

Abstract: Factor H, a secretory glycoprotein composed of 20 short consensus repeat modules, is an inhibitor of the complement system. Previous studies of inherited factor H deficiency revealed single amino acid substitutions at conserved cysteine residues, on one allele arginine for cysteine 518 (C518R) and on the other tyrosine for cysteine 941 (C941Y) (Ault, B. H., Schmidt, B. Z., Fowler, N. L., Kashtan, C. E., Ahmed, A. E., Vogt, B. A., and Colten, H. R. (1997) J. Biol. Chem. 272, 25168 -25175). To ascertain if the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0
5

Year Published

2000
2000
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 52 publications
2
25
0
5
Order By: Relevance
“…Since in the present case no circulating abnormal factor H protein was detected by Western blot, we propose that folding and secretion of this protein is impaired, resulting in its retention in the cytoplasm, as previously reported [12,13]. However, the genetic abnormality did not affect CFHL1 secretion because it was localized far from the complement factor H exon 10, at the 3 0 end of the gene.…”
Section: Discussionsupporting
confidence: 56%
“…Since in the present case no circulating abnormal factor H protein was detected by Western blot, we propose that folding and secretion of this protein is impaired, resulting in its retention in the cytoplasm, as previously reported [12,13]. However, the genetic abnormality did not affect CFHL1 secretion because it was localized far from the complement factor H exon 10, at the 3 0 end of the gene.…”
Section: Discussionsupporting
confidence: 56%
“…Intriguingly, an earlier report concerned a patient with severe Cfh deficiency in association with type 3 collagen glomerulopathy 82 (more likely representing chronic thrombotic microangiopathy 16 ) in whom a different homozygous missense mutation was identified at the same site on SCR 16 83 . The substitution of a cysteine residue (in this case with a tyrosine) altered the secondary structure of the Cfh protein, resulting in its nonsecretion 84 . A young girl was reported with macroscopic hematuria, very low C3 and Cfh levels, and endocapillary GN with predominant glomerular C3 85 .…”
Section: Pathogenesismentioning
confidence: 96%
“…They showed that these factor H mutants were retained in the endoplasmic reticulum. This suggests that the factor H deficiency in this patient was in fact due to impaired factor H secretion [117].…”
Section: Human Deficiency Of Factor Hmentioning
confidence: 99%